An isoindigo containing donor–acceptor polymer: synthesis and photovoltaic properties of all-solution-processed ITO- and vacuum-free large area roll-coated single junction and tandem solar cells1. Issue 8 (28th February 2015) - Brandt, Rasmus Guldbaek; Yue, Wei; Andersen, Thomas Rieks; Larsen-Olsen, Thue Trofod; Hinge, Mogens; Bundgaard, Eva; Krebs, Frederik C.; Yu, Donghong
<x xml:space="preserve">Abstract</x> A novel isoindigo containing D–A polymer was developed for large area single junction and tandem solar cells.